What is coaching in cancer care? : an exploratory qualitative study with coaches and healthcare professionals - Gérain, Pierre; Jacquet, Wolfgang; Tanious, René; Van Hoof, Elke (International Journal of Evidence Based Coaching and Mentoring)
Cancer patients face multiple challenges, and coaching has emerged as a promising psychosocial support approach. This study explores how healthcare professionals and coaches view the definition, role, and integration of coaching within cancer care. Through thematic analysis of responses from 13 healthcare professionals and five coaches in French-speaking Belgium, findings show both groups see coaching as valuable psychosocial support but differ in their view of the role of coaching. Healthcare professionals view coaches as first-line providers, while coaches stress empowerment and post-treatment support. Addressing this discrepancy is essential for establishing a necessary foundation to guide both the implementation and evaluation of coaching in oncology care.